Falling HIV incidence in a community clinic cohort of men who have sex with men and transgender women in Barcelona, Spain. (August 2020) - Meulbroek, Michael; Dalmau-Bueno, Albert; Saz, Jorge; Marazzi, Giovanni; Pérez, Fèlix; Coll, Josep; Taboada, Héctor; Pujol, Ferran
In Barcelona, Spain prior to 2006, HIV testing was mostly limited to formal healthcare facilities with no incidence data reported. A community-based organization (BCN Checkpoint) was established to increase HIV testing in a peer-led community location to generate incidence data in men who have sex with men and transgender women. Three community engagement interventions were conducted between 2009 and 2017 as follows: 2009–2011 (peer-led point-of-care testing for HIV), 2012–2014 (12-monthly HIV testing with an emphasis on testing in partnerships), 2015–2017 (three-monthly HIV testing with rapid referral for antiretroviral initiation). Between 2009 and 2017 a predominantly cisgender male (99.4%) and Spanish national (62.4%) population with mean age of 34.8 years had 49, 630 visits. Mean visit number increased from 1.69 in the first to 2.07 in the last three-year period. HIV incidence fell from 4.17 (95% confidence interval [CI]: 3.53–4.93) per 100 person-years in 2009–2011 to 1.57 (95% CI: 1.30–1.89) per 100 person-years in 2015–2017. This represents a 62% reduction (incidence rate ratio: 0.38, 95% CI: 0.29–0.48) between the first and third study period (p < 0.001). These early interventions may have contributed to the reduction seen in HIV incidence in this cohort.